EVALUASI KETAHANAN TURUNAN DARI BEBERAPA SILANGAN GLADIOL TERHADAP FUSARIUMPADA TINGKAT SEMAIAN - Bakhtiar Basyah (Jurnal Floratek, 2006)
Evaluation of Resistance to Fusarium at Seedling Stage of  Several Hybrids Gladiolus Bakhtiar, Hajrial Aswidinnoor, dan Toto Sutater ABSTRACTOne of the major problems in flower and corms production of gladiolus is wilt diseases and corm rot caused by Fusarium oxysporum f.sp. gladiolii. Therefore, the development of resistant gladiolus cultivars through breeding programs is highly desired to overcome these diseases. The seedling tests make it possible to obtain new gladiolus cultivars with high levels of fusarium resistance. The objective of this experiment were to develop a seedling test for early selection of Fusarium resistance in gladiolus and to evaluate the levels of fusarium resistance of hybrids produced at seedling stage. Screening for fusarium resistance in seedling populations that using ± 103 propagules per gram of soil could be conducted at 8 weeks after sowing. Queen Occer x 623-1, 646-15 x 623-1 and 623-1 x Queen Occer crosses gave more resistant progeny than the others.